Paisajes sonoros e identidad en la juventud indígena Bribrí - Paz Barahona, Carlos (2016)
The condition of youth in ethnic bribrí moves between two paths that oppose and relate on the one hand, expectations of a national political agenda for the conservation of indigenous cultural identity that matches with the local initiatives of identity affirmation of the same the loss of indigenous traditions and cultural heritage and, on the other hand, the expansion of the media and tourism have taken the young bribrís a huge amount of consumer goods, including music from other latitudes like young people and makes them feel young inserted in the historic moment was built by the media and perceived by them as dynamic and current.